Tumor microbiome differences in early-onset versus average-onset pancreatic adenocarcinoma☆ - T. Jayakrishnan; N. Sangwan; K.G. Nair; S.D. Kamath; M.H. Patel; D. Joyce; M. Walsh; R. Simon; D. Vadehra; R.V. Iyer; C. Fountzilas; A.A. Khorana (ESMO Gastrointestinal Oncology, 2025)
Background: Compelling evidence supports the biomarker potential of microbiome in pancreatic adenocarcinoma. Given the knowledge gap on the characteristics and significance of microbiome in early-onset pancreatic ductal adenocarcinoma (eoPDAC, age <50 years), we aimed to evaluate microbiome profiles in resected specimens from individuals with eoPDAC and average-onset PDAC (aoPDAC, age >50 years). Materials and methods: We carried out shotgun metagenomic sequencing in resected specimens from individuals with eoPDAC (n = 24) and aoPDAC (n = 20). Statistical tests included Wilcoxon test, permutational analysis of variance, multiomic classifier modeling, differential abundance analysis, and linear regression. All P values were adjusted for multiple testing and P < 0.05 was considered statistically significant. Results: We successfully sequenced several bacteria and fungi in the tumor specimens from 44 individuals with resected PDAC (24 eoPDAC and 20 aoPDAC). The alpha diversity of the bacterial microbiome was higher in eoPDAC tumor tissue compared with aoPDAC (P = 0.04). In contrast, the fungal mycobiome’s alpha diversity was higher for aoPDAC tumor tissue (P = 0.02). Key organisms with differential abundance between tumor tissue from individuals with eoPDAC and aoPDAC included Bacillus, Candida, Collimonas, Cupriavidus, Enterobacter, Escherichia, Klebsiella, Malasseiza, Mucilaginibacter, Neisseria, and Sphingomonas. Higher bacterial diversity in tumor tissue was associated with better overall survival for individuals with eoPDAC (R = 0.26, P = 0.02). Conclusions: Shotgun metagenomic sequencing identified bacterial microbiome and fungal mycobiome in tumors from individuals with eoPDAC and aoPDAC. We observed significant differences in alpha and beta diversity and relative abundances of organisms suggesting distinct microbiome signatures. Microbiome associations with survival were observed in eoPDAC indicating unique potential as prognostic biomarker.